Psychometric Properties of the Medical Mistrust Index (MMI) in Latina Immigrants. Issue 2 (3rd April 2019) - Sheppard, Vanessa B.; Huei-Yu Wang, Judy; Hurtado-de-Mendoza, Alejandra; Sutton, Arnethea L.; LaVeist, Thomas A.
Abstract: Medical mistrust measures have not been validated in Latino immigrants. This study examined the psychometric properties of the Medical Mistrust Index and its association with health care satisfaction in a sample of Latina immigrants. Participants were 168 self-identified Latinas ≥40 years old. Women were recruited from three Latino-serving health clinics and through a Latino radio program. A bilingual interviewer administered the Medical Mistrust Index in Spanish along with items pertaining to sociodemographic and health care factors. Principal component extraction method was used to evaluate internal consistency reliability to examine Medical Mistrust Index underlying factors. Construct validity was assessed by analyzing the relationship between the Medical Mistrust Index with three related measures (racism, discrimination, trust in doctors). To assess the criterion validity of the Medical Mistrust Index, a logistic regression model examined whether medical mistrust was associated with Latina women's satisfaction with health care controlling for sociodemographic and health care factors. Participants were 51 years old on average, around half had completed High school or less and were uninsured. Most were monolingual Spanish speakers. Two factors: competence and suspicion explained 40% of the total Medical Mistrust Index variance. Internal consistency was favorable and construct validity was supported. Results support the reliability and validity of the Medical Mistrust Index and its association with Latina's satisfaction with health care.